THE FISCAL POLICY KEY CHALLENGES IN THE CONDITIONS OF RUSSIAN FEDERATION ECONOMY FALLING - M. Ibrahim (Вестник университета)
In the article the author considers key problems of fiscal policy of the Russian Federation. In general, it is noted that fiscal policy acts as the regulator of the state expenses and taxes, and only the correct use of instruments of fiscal policy conducts to the stable, counterbalanced and prospering conduct of life of all federation entities. Besides, the general conclusion that fiscal policy acts as the regulator of the state expenses and taxes is formulated.